2022
DOI: 10.1124/jpet.121.001048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiling of Antifentanyl Monoclonal Antibodies in Combination with Naloxone in Pre- and Postexposure Models of Fentanyl Toxicity

Abstract: The incidence of fatal drug overdoses in the United States is an alarming public health threat that has been exacerbated by the COVID-19 pandemic, resulting in over 100,000 deaths between April 2020 and April 2021. A significant portion of this is attributable to widespread access to fentanyl and other synthetic opioids, alone or in combination with heroin or psychostimulants such as cocaine or methamphetamine. Monoclonal antibodies (mAb) offer prophylactic and therapeutic interventions against opioid overdose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…All mAbs significantly reduced brain fentanyl and increased fentanyl concentration in serum, though HY11-6B2_Ch was least effective at sequestering fentanyl in serum. Because HY6-F9_Mu has previously shown efficacy in rats, 19 , 40 the efficacy of HY6-F9_Ch was also compared to HY6-F9_Mu in rats ( Figure 3 ). Rats were passively immunized with 40 mg/kg of HY6-F9_Mu or HY6-F9_Ch, and 24 hours later challenged with 0.1 mg/kg fentanyl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All mAbs significantly reduced brain fentanyl and increased fentanyl concentration in serum, though HY11-6B2_Ch was least effective at sequestering fentanyl in serum. Because HY6-F9_Mu has previously shown efficacy in rats, 19 , 40 the efficacy of HY6-F9_Ch was also compared to HY6-F9_Mu in rats ( Figure 3 ). Rats were passively immunized with 40 mg/kg of HY6-F9_Mu or HY6-F9_Ch, and 24 hours later challenged with 0.1 mg/kg fentanyl.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-fentanyl murine mAb and chAb isolated by other groups have been shown to prevent fentanyl-induced antinociception and brain distribution at similar mAb and fentanyl doses to those used here. 20 , 21 Meanwhile, HY6-F9_Mu has been shown to prevent fentanyl effects in both mice and rats, 19 and to reverse respiratory depression in rats, 40 a more clinically relevant measure for fentanyl overdose than antinociception. However, as murine and chimeric mAbs are unsuitable for human use due to ADA responses, 26–28 humanization is essential for clinical advancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1A and B) (Raleigh et al, 2019;Robinson et al, 2020;Crouse et al, 2022). After sortase A-mediated conjugation of fen-sort to the surface VSG (Fent-VAST), sortagging efficiency was assessed by flow cytometry using a mouse anti-fentanyl mAb (Baehr et al, 2020(Baehr et al, , 2022. This revealed that 100% of the trypanosomes had been decorated with the fent-sort (Figure 2A).…”
Section: The Vast Platform Induces Antibody Titers Protective Against...mentioning
confidence: 99%
“…These strategies have also been used to generate mAbs against a variety of target drugs of abuse including fentanyl. Notably, fentanyl-specific mAbs are effective in both preventing and reversing fentanyl's pharmacological effects in rodent models, further highlighting the promise of immunotherapeutics in the opioid space (Smith et al, 2019;Baehr et al, 2020Baehr et al, , 2022Ban et al, 2021). While promising indeed, there remains a lack of clinical output in this space and a desperate need for additional intervention options.…”
Section: Introductionmentioning
confidence: 99%